THE SOCIAL-ECONOMIC SIGNIFICANCE AND PLACE OF PILGRIMAGE TOURISM IN THE KASHKADARYA REGION - Uzokov, Jamshid (Innovatsion texnologiyalar, 2024)
This article highlights the factors of the development of pilgrimage tourism and reveals the socio-economic importance and role of internal, external, religious and secular pilgrimages.